Intraoperative measurement of the respiratory exchange ratio predicts postoperative complications after liver transplantation - Sean Coeckelenbergh; Olivier Desebbe; François Martin Carrier; Francois Thepault; Cécile De Oliveira; Florian Pellerin; Cyril Le Canne; Laurence Herboulier; Edita Laukaityte; Maya Moussa; Leila Toubal; Hiromi Kato; et al. (BMC Anesthesiology, 2022)
Abstract Background During surgery, any mismatch between oxygen delivery (DO2) and consumption (VO2) can promote the development of postoperative complications. The respiratory exchange ratio (RER), defined as the ratio of carbon dioxide (CO2) production (VCO2) to VO2, may be a useful noninvasive tool for detecting inadequate DO2. The primary objective of this study was to test the hypothesis that RER measured during liver transplantation may predict postoperative morbidity. Secondary objectives were to assess the ability of other variables used to assess the DO2/VO2 relationship, including arterial lactate, mixed venous oxygen saturation, and veno-arterial difference in the partial pressure of carbon dioxide (VAPCO2gap), to predict postoperative complications. Methods This retrospective study included consecutive adult patients who underwent liver transplantation for end stage liver disease from June 27th, 2020, to September 5th, 2021. Patients with acute liver failure were excluded. All patients were routinely equipped with a pulmonary artery catheter. The primary analysis was a receiver operating characteristic (ROC) curve constructed to investigate the discriminative ability of the mean RER measured during surgery to predict postoperative complications. RER was calculated at five standardized time points during the surgery, at the same time as measurement of blood lactate levels and arterial and mixed venous blood gases, which were compared as a secondary analysis. Results Of the 115 patients included, 57 developed at least one postoperative complication. The mean RER (median [25–75] percentiles) during surgery was significantly higher in patients with complications than in those without (1.04[0.96–1.12] vs 0.88[0.84–0.94]; p < 0.001). The area under the ROC curve was 0.87 (95%CI: 0.80–0.93; p < 0.001) with a RER value (Youden index) of 0.92 giving a sensitivity of 91% and a specificity of 74% for predicting the occurrence of postoperative complications. The RER outperformed all other measured variables assessing the DO2/VO2 relationship (arterial lactate, SvO2, and VAPCO2gap) in predicting postoperative complications. Conclusion During liver transplantation, the RER can reliably predict postoperative complications. Implementing this measure intraoperatively may provide a warning for physicians of impending complications and justify more aggressive optimization of oxygen delivery. Further studies are required to determine whether correcting the RER is feasible and could reduce the incidence of complications.